ANALISIS PENGENDALIAN STRATEGIS DALAM MENDUKUNG PENCAPAIAN TUJUAN ORGANISASI DI PT INDONESIA AIRASIA - Ega Novriyela; Restia Pramesti; Lulu Cantika Puteri; Delviana Citra (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
The airline industry is one of the most dynamic business sectors due to intense competition, fluctuating fuel prices, regulatory changes, and rapid technological developments. Therefore, companies need effective strategic control systems to ensure that organizational objectives can be achieved efficiently. This study aims to analyze the role of strategic control in supporting the achievement of organizational goals at PT Indonesia AirAsia. The research employed a descriptive qualitative approach using secondary data obtained through literature studies, company reports, journals, and relevant academic references. The analysis focuses on the relationship between corporate strategy, business unit strategy, management style, and strategic control mechanisms implemented by the company. The findings indicate that PT Indonesia AirAsia successfully implements a Cost Leadership strategy supported by efficient operational management, digital transformation, and adaptive management practices. Strategic control is conducted through the monitoring of key performance indicators such as Cost per Available Seat Kilometer (CASK), Load Factor, and On-Time Performance (OTP). The study concludes that strategic control plays a crucial role in maintaining alignment between corporate strategy, business unit strategy, and management style, enabling the company to achieve organizational objectives effectively and sustain its competitive advantage in the low-cost carrier industry.